Protein Kinase B/Akt Binds and Phosphorylates PED/PEA-15, Stabilizing Its Antiapoptotic Action - Trencia, Alessandra (American Society for Microbiology, 2003)
The antiapoptotic protein PED/PEA-15 features an Akt phosphorylation motif upstream from Ser(116). In vitro, recombinant PED/PEA-15 was phosphorylated by Akt with a stoichiometry close to 1. Based on Western blotting with specific phospho-Ser(116) PED/PEA-15 antibodies, Akt phosphorylation of PED/PEA-15 occurred mainly at Ser(116). In addition, a mutant of PED/PEA-15 featuring the substitution of Ser(116)→Gly (PED(S116→G)) showed 10-fold-decreased phosphorylation by Akt. In intact 293 cells, Akt also induced phosphorylation of PED/PEA-15 at Ser(116). Based on pull-down and coprecipitation assays, PED/PEA-15 specifically bound Akt, independently of Akt activity. Serum activation of Akt as well as BAD phosphorylation by Akt showed no difference in 293 cells transfected with PED/PEA-15 and in untransfected cells (which express no endogenous PED/PEA-15). However, the antiapoptotic action of PED/PEA-15 was almost twofold reduced in PED(S116→G) compared to that in PED/PEA-15(WT) cells. PED/PEA-15 stability closely paralleled Akt activation by serum in 293 cells. In these cells, the nonphosphorylatable PED(S116→G) mutant exhibited a degradation rate threefold greater than that observed with wild-type PED/PEA-15. In the U373MG glioma cells, blocking Akt also reduced PED/PEA-15 levels and induced sensitivity to tumor necrosis factor-related apoptosis-inducing ligand apoptosis. Thus, phosphorylation by Akt regulates the antiapoptotic function of PED/PEA-15 at least in part by controlling the stability of PED/PEA-15. In part, Akt survival signaling may be mediated by PED/PEA-15.